Students’ Beliefs and Attitudes in Exploring Critical Literacy Comprehension towards Online Media Information into their Writing Practices - Riwayatiningsih, Rika (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Addressing critical literacy exploration into students’ language learning is perpetuated in this digital media- dependent environment. Reading and writing competencies have also pertained the critical enactment in order to present the beyond textual values. Through class discussions and class observations among 12 tertiary English major students in a private university in Indonesia, this study explores students’ beliefs and attitudes towards their critical literacy comprehension on online media information through writing practices. This exploratory case study collect the data covering the recordings of class discussions and class observations from student lesson implementation during their writing course. The results of this study reveal that most of the students are aware of the critical understanding of particular information conveyed from certain messages in their written works. Their beliefs on critical literacy agency has raised several attitudes of how they construct the social perspectives based on selections of what to include and exclude in their written texts. The article is also present recommendation to enlighten the learning in a critical stance.